El uso de reacciones de PCR anidadas mejora la tipificación genética de Mycoplasma hyopneumoniae a partir de diferentes muestras clínicas - Rebaque, F. (2016)
It is important to identify distinct Mycoplasma hyopneumoniae genotypes to improve the study and understanding of some epidemiological aspects of the disease it produces. MLVA (Multiple-Locus Variable-number tandem repeats Analysis) methodology would be the most adequate for typing this pathogen from clinical samples. The objective of the present study was to design nested PCR assays for VNTR (Variable Number of Tandem Repeats) loci P97, H4, and H5 with the aim to obtain a high analytical sensitivity. To evaluate them, DNA samples positive for M. hyopneumoniae were analyzed by the nested PCR assays in parallel to conventional PCR assays, and the proportion of positive results with each approach were compared. Taking into account the higher sensitivity of the PCR assays developed in this study, it was concluded that the recommended approach to type M. hyopneumoniae from clinical samples ? even when they contain a low load of the agent? is to perform nested PCR assays for these loci, along with the other one previously informed for P146.